Vaccination dropout and associated factors among children in Ethiopia: a systematic review and meta-analysis (2014–2024) - Eyasu Bamlaku Golla; Habtamu Geremew; Alegntaw Abate; Mohammed Ahmed Ali; Mulat Belay Simegn; Werkneh Melkie Tilahun; Samuel Abdisa Kuse; Smegnew Gichew Wondie (BMC Pediatrics)
Abstract Background Children in sub-Saharan Africa, particularly in Ethiopia, continue to suffer from vaccine-preventable diseases (VPDs), contributing to child mortality. One of the key challenges is vaccination dropout, where children fail to receive subsequent doses after the initial vaccine, leading to incomplete immunization coverage. Hence, our review aimed to determine the pooled magnitude of vaccination dropout and the factors associated with it among children in Ethiopia. Method A comprehensive search of relevant studies was conducted through electronic web-based international databases and the institutional repository of Ethiopian universities. Data were extracted via a Microsoft Excel spreadsheet and then exported to STATA 17 for statistical analysis. A checklist from the Joanna Briggs Institute was utilized to assess the quality of the studies. A random-effects model was employed to estimate the pooled magnitude of vaccination dropout. Heterogeneity between studies was evaluated via the I-square test. Funnel plots and Egger’s regression test were utilized to assess publication bias. Results Seventeen articles with a total sample size of 9152 children (12–23 months old) were included in this meta-analysis. Consequently, the pooled magnitude of vaccination dropout from BCG to measles and Penta-1 to Penta-3 among children aged 12–23 months in Ethiopia was 16.93% (95% CI: 12.43, 21.44) and 13.16% (95% CI: 8.37, 17.96) respectively. Mothers who did not attend ANC (AOR = 3.58, 95% CI = 1.99, 6.44), postponed immunization schedule (AOR = 2.73, 95% CI = 1.53, 4.87), distance from the health care facility (AOR = 2.46, 95% CI = 2.01, 17.18), and home delivery (AOR = 2.78, 95% CI = 2.28, 3.38) were identified as significant factors associated with vaccine dropout. Conclusion The overall pooled magnitude of vaccination dropout among children in Ethiopia is greater than the WHO recommendation of less than 10%. Therefore, our findings suggest the necessity of counseling and educating women to attend antenatal care (ANC) follow-ups, give birth at healthcare facilities, and provide mobile and outreach immunization services for remote areas.